Kehidupan Penambang Timah Inkonvensional Di Desa Nibung Kecamatan Koba Kabupaten Bangka Tengah Provinsi Bangka Belitung - Syahda, Niesa Almeira; Kadarisman, Yoskar (Peneliti.net, 2024)
This study aims to determine the life of unconventional tin miners in Nibung Village, Koba District, Central Bangka Regency, Bangka Belitung Province. The research was conducted using qualitative research methods and data collection techniques in the form of interviews, observations and documentation. The subjects in this study were selected using purposive sampling techniques with the number of informants as many as 6 people. The results showed that the life of unconventional tin miners became better than their previous lives. The existence of unconventional tin mines in Nibung Village also causes social relations. Social relations that occur are between fellow unconventional tin miners, unconventional tin miners with conventional tin mine owners and also unconventional tin miners with the surrounding community, namely in Nibung Village. Since the existence of unconventional tin mines, the economy of unconventional tin miners has increased. The miners can provide for their families on a daily basis. Not only miners who experience economic improvement but also the surrounding community also experience the same thing. The community also felt that their economy increased after the existence of an unconventional tin mine in Nibung Village. The existence of unconventional tin mining in Nibung Village also has an impact on miners, the community and also the surrounding environment. The impact caused is a positive and negative impact. In addition, because this unconventional tin mine does not get an official permit from the government, the unconventional tin mine in Nibung Village is often carried out routine raids by government officials to stop unconventional tin miners or illegal miners who do not have permits to mine.